CD8+ T-Cells as Immune Regulators of Multiple Sclerosis - Sinha, Sushmita; Boyden, Alexander W.; Itani, Farah R.; Crawford, Michael P.; Karandikar, Nitin J. (Frontiers in Immunology, 2015)
The vast majority of studies regarding the immune basis of MS (and its animal model, EAE) has largely focused on CD4+ T-cells as mediators and regulators of disease. Interestingly, CD8+ T-cells represent the predominant T-cell population in human MS lesions and are oligoclonally expanded at the site of pathology. However, their role in the autoimmune pathologic process has been both understudied and controversial. Several animal model and MS patient studies support a pathogenic role for CNS-specific CD8+ T-cells, whereas we and others have demonstrated a regulatory role for these cells in disease. In this review, we describe studies that have investigated the role of CD8+ T-cells in MS and EAE, presenting evidence for both pathogenic and regulatory functions. In our studies, we have shown that cytotoxic/suppressor CD8+ T-cells are CNS antigen-specific, MHC class I-restricted, IFNγ- and perforin-dependent, and are able to inhibit disease. The clinical relevance for CD8+ T-cell suppressive function is best described by a lack of their function during MS relapse, and importantly, restoration of their suppressive function during quiescence. Further, CD8+ T-cells with immunosuppressive functions can be therapeutically induced in MS patients by glatiramer acetate (GA) treatment. Unlike CNS-specific CD8+ T-cells, these immuno-suppressive GA-induced CD8+ T-cells appear to be HLA-E-restricted. These studies have provided greater fundamental insight into the role of autoreactive as well as therapeutically-induced CD8+ T-cells in disease amelioration. The clinical implications for these findings are immense and we propose that this natural process can be harnessed towards the development of an effective immunotherapeutic strategy.